2019
DOI: 10.3389/fmicb.2019.02887
|View full text |Cite
|
Sign up to set email alerts
|

Soil Microbial Networks Shift Across a High-Elevation Successional Gradient

Abstract: While it is well established that microbial composition and diversity shift along environmental gradients, how interactions among microbes change is poorly understood. Here, we tested how community structure and species interactions among diverse groups of soil microbes (bacteria, fungi, non-fungal eukaryotes) change across a fundamental ecological gradient, succession. Our study system is a high-elevation alpine ecosystem that exhibits variability in successional stage due to topography and harsh environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 96 publications
1
7
1
Order By: Relevance
“…Intriguingly and contrary to the previous conclusion that temperature had a stimulating effect on the microbes (Farrer et al, 2019), we found that the relative abundances of most of the target genes were higher in the nongrowing (winter) than the growing (summer) season (Figure 4; Table S5). Soil temperature was also not significantly correlated with P availability across sites and seasons (Figure S3).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Intriguingly and contrary to the previous conclusion that temperature had a stimulating effect on the microbes (Farrer et al, 2019), we found that the relative abundances of most of the target genes were higher in the nongrowing (winter) than the growing (summer) season (Figure 4; Table S5). Soil temperature was also not significantly correlated with P availability across sites and seasons (Figure S3).…”
Section: Discussioncontrasting
confidence: 99%
“…On the one hand, wetland salinization strongly affected the physicochemical characteristics of the soil water (Table S3), which can induce a strong selection pressure on soil microbial communities, thereby excluding many microbes from the network (Ratzke et al, 2020). On the other hand, previous studies have reported that high microbial diversity generally implies that rich microbial communities simultaneously compete for the same resources and energy within their habitats, which is accompanied by low network complexity (Farrer et al, 2019;Gao et al, 2022), consistent with the high microbial diversity we observed in the brackish wetland (Figure 2).…”
Section: Response Of P-cycling Microbial Genes To Salinitymentioning
confidence: 99%
“…3; Table 3). The main local filters were spatial distance and elevation, which together explained 46.8% of the total variation, the same as found in previous biogeographic studies (Fierer and Jackson 2006;Pellissier et al 2014;Wang et al 2017;Farrer et al 2019), with a secondary effect of the season (Goss-Souza et al 2017;Ma et al 2017), biopores, an abiotic soil physical factor. The average weighted degree was the major biotic filter of bacterial communities at the local scale (11.9%), corroborating the findings of a biogeographic study of bacterial communities in paddy soils at a continental 32 scale (Gao et al 2019).…”
Section: Drivers Of Bacterial Assembly Patterns and Processes Across ...supporting
confidence: 81%
“…However, associations between Dehalococcoidia and sulfate‐reducing bacteria in Deltaproteobacteria were identified in deep sediments, suggesting that sulphate‐reducing activity may enhance dechlorination by Dehalococcoidia (May et al, 2008). Other studies have suggested that carbon inputs and shifts in carbon resource increased network complexity (Farrer et al, 2019; Shi et al, 2016), which could possibly explain the drastic increase of interactions in the network of 30–90 cm, as increased TOC and distinct δ 13 C was detected at ~50 cm. These results indicated that terrestrial inputs may also influence the structure of microbial co‐occurrence networks.…”
Section: Discussionmentioning
confidence: 91%